2015
DOI: 10.1108/amhid-01-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Historical and clinical items of the HCR-20 as predictors of risk within an intellectual disability population

Abstract: Purpose -The use of violence risk assessment measures within intellectual disabilities (ID) services is now the norm and a growing target for research. The purpose of this paper is to examine the clinical utility of the historical and clinical factors of the HCR-20 in predicting violence. Design/methodology/approach -The study took place within a national low secure service for adults with ID examining all completed admissions over a six-year period, (N ¼ 22). Clinical records covering the first three months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The HCR-20 V3 assessment is based upon the evaluator assembling a sufficient information base upon which to make ratings of risk factors, and why they have led a person to be violent, which typically involves an interview with the patient being evaluated, plus a review of case files (Douglas et al, 2014). A number of studies have investigated the predictive validity of the HCR-20 in ID populations in regard to institutional aggression (Chaplin, Eyeoyibo, Wright, Xenitidis and McCarthy, 2015;Fitzgerald et al, 2013;O'Shea et al, 2015) and future reconviction (Gray et al, 2007), and reported equivalent, or higher levels of validity in the ID population as compared to the general forensic population. This measure was chosen for the study due to its inclusion of age data within the scores and qualitative evidence provided for two items: H1 -History of Problems with Violence and H2 -History of Problems with Other Antisocial Behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…The HCR-20 V3 assessment is based upon the evaluator assembling a sufficient information base upon which to make ratings of risk factors, and why they have led a person to be violent, which typically involves an interview with the patient being evaluated, plus a review of case files (Douglas et al, 2014). A number of studies have investigated the predictive validity of the HCR-20 in ID populations in regard to institutional aggression (Chaplin, Eyeoyibo, Wright, Xenitidis and McCarthy, 2015;Fitzgerald et al, 2013;O'Shea et al, 2015) and future reconviction (Gray et al, 2007), and reported equivalent, or higher levels of validity in the ID population as compared to the general forensic population. This measure was chosen for the study due to its inclusion of age data within the scores and qualitative evidence provided for two items: H1 -History of Problems with Violence and H2 -History of Problems with Other Antisocial Behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…This remains an important area for investigation, not least because of the absence of SPJ risk assessment tools developed for use in assessing people with developmental disorders. While there is a growing body of research to support the predictive validity of existing SPJ tools for adults with developmental disorders (Chaplin et al, 2015;Lindsay et al, 2008), research is yet to validate the use of the adolescent Structured Assessment of Violence Risk in Youth [SAVRY] (Borum et al, 2006) tool, for developmental disorder populations. Whether risk ratings on the SAVRY, which includes trauma items, are reflected in more frequent or severe displays of risk behaviours or a greater need for restrictive practices is an important area for exploration and represents a critical oversight in the literature.…”
Section: The Role Of Trauma In Risk Assessmentmentioning
confidence: 99%
“…ex., mesure de la stabilité émotionnelle, évaluation du risque, opportunité de choix). Elle comprend, par exemple, un outil d'évaluation de gestion du risque des comportements sexuels abusifs chez les personnes présentant une DI hébergées en communauté (Cookman, 2012) et des outils d'évaluation des risques (Arborelius, Fors, Svensson, Sygel et Kristiansson, 2013;Chaplin, Eyeoyibo, Wright, Xenitidis et McCarthy, 2015;Pouls et Jeandarme, 2016;Taylor et Novaco, 2013). Une seule des études recensées intègre une procédure incluant un groupe contrôle (Arborelius et al, 2013).…”
Section: Méthodeunclassified